Efficacy and dermal tolerance of a novel alcohol‐based skin antiseptic in horses. Issue 4 (14th April 2018) - Tannahill, Victoria J.; Cogan, Tristan; Allen, Kate; Acutt, Elizabeth; Busschers, Evita
Abstract: Objective: To determine the efficacy and dermal tolerance of a novel alcohol‐based skin antiseptic (ABSA) in horses. Study Design: Experimental study. Animal Population: Systemically healthy horses (n = 25) with no history or clinical signs of skin disease. Methods: Four clipped sites on the abdomen were randomly assigned to a skin preparation protocol: saline (negative control; NC), chlorhexidine gluconate followed by isopropyl alcohol (positive control; PC), saline followed by the ABSA (ABSA A), or a commercially available horse shampoo followed by the ABSA (ABSA B). Microbiological swabs were obtained from each site and cultured on MacConkey and mannitol salt agar plates. Colony‐forming units were counted 18‐24 hours later. All sites were scored for signs of skin reaction before, immediately after, 1 hour after, and 24 hours after skin preparation. Results: The PC, ABSA A, and ABSA B methods reduced skin microbial burden compared with the NC method ( P  < .001), but no difference was detected between antiseptic products. Preparation time did not differ between ABSA A and ABSA B methods ( P  = 0.108); both were faster than the PC method ( P  < 0.001 for both). Skin reactions were most abundant 24 hours after skin preparation (30.5%), but there was no significant association with antiseptic used, and no horses required veterinary treatment. Conclusion: The ABSA preparations tested in this study were as effective and well tolerated as a chlorhexidine gluconate‐based method, but required less time in healthy horses. Clinical significance: The ABSA tested here provides an efficacious, fast‐acting, and well‐tolerated alternative to achieve skin antisepsis in healthy horses. These results justify further investigation in clinical cases.